Complex molecular mechanisms underlying MYMIV-resistance in Vigna mungo revealed by comparative transcriptome profiling - Kundu, Anirban (Sci Rep, 2019)
Mungbean Yellow Mosaic India Virus (MYMIV)-infection creates major hindrance in V. mungo cultivation and poses significant threat to other grain legume production. Symptoms associated include severe patho-physiological alterations characterized by chlorotic foliar lesion accompanied by reduced growth. However, dissection of the host’s defense machinery remains a tough challenge due to limited of host’s genomic resources. A comparative RNA-Seq transcriptomes of resistant (VM84) and susceptible (T9) plants was carried out to identify genes potentially involved in V. mungo resistance against MYMIV. Distinct gene expression landscapes were observed in VM84 and T9 with 2158 and 1679 differentially expressed genes (DEGs), respectively. Transcriptomic responses in VM84 reflect a prompt and intense immune reaction demonstrating an efficient pathogen surveillance leading to activation of basal and induced immune responses. Functional analysis of the altered DEGs identified multiple regulatory pathways to be activated or repressed over time. Up-regulation of DEGs including NB-LRR, WRKY33, ankyrin, argonaute and NAC transcription factor revealed an insight on their potential roles in MYMIV-resistance; and qPCR validation shows a propensity of their accumulation in VM84. Analyses of the current RNA-Seq dataset contribute immensely to decipher molecular responses that underlie MYMIV-resistance and will aid in the improvement strategy of V. mungo and other legumes through comparative functional genomics.